The Inhibition Effect of Peach Juice on Corrosion of Low Carbon Steel in Hydrochloric Acid at Different Temperatures - S. Yaro, Aprael; F. Ibraheem, Hadeel (Iraqi Journal of Chemical and Petroleum Engineering, 2010)
The corrosion inhibition of low carbon steel in1N HCl solution in the presence of peach juice at temperature (30,40,50,and 60)°C at concentration ( 5, 10, 20, 30, 40and 50 cm3/L)were studied using weight loss and polarization techniques. Results show that the inhibition efficiency was increased with the increase of inhibitor concentration and increased with the increase of temperature up to 50ºC ,above 50ºC (i.e. at 60 ºC) the values of efficiency decreases. Activation parameters of the corrosion process such as activation energies, Ea, activation enthalpies, ΔH, and activation entropies, ΔS, were calculated. The adsorption of inhibitor follows Langmuir isotherm. Maximum inhibition efficiency obtained was a bout 91% at 50ºC in the 50 cm3/L inhibitor concentration. The polarization curves show that peach Juice is a mixed inhibitor.